Reduction Of Sulphate In Waste Recycle Aggregate Using Bacillus Subtilis - Abdul Aziz, Nurhanim (2018)
Waste concrete aggregate (WCA) is highly potential to be re-utilised as a recycled material as it is applicable to numerous functions. Attached cement paste on WCA surface has limited the potential WCA to be recycled as a part of raw construction materials. Low density, high in water absorption and sulphate content are identified as the major contributing factors for this limitation. The sulphate content in delayed ettringite formation (DEF) from high water absorption of attached cement paste leads to DEF expansion and forms a micro-crack, causing a mass loss and affects the mechanical strength (compressive strength) of the concrete.